THE INTERRELATION BETWEEN THE HAFIZ AND THE INSTRUMENT IN MAKAM PERFORMANCE - Feruza Abdukarimova (Western European Studies, 2025)
Uzbek national musical art, particularly the classical makam performance, is one of the most comprehensive branches of traditional music. Each aspect of this art — whether vocal (xonandalik) or instrumental (sozandalik) performance — complements the other, creating a complete and harmonious expression. This article provides an overview of the concept of the “hafiz” title in traditional vocal art, discusses the main requirements for achieving this status, highlights the contributions of prominent hafiz masters of the past, and analyzes the interaction between the singer and the instrumentalist as well as its significance for performance mastery.
Keywords: makam; Qur’an al-Karim; hafiz; performance